2015
DOI: 10.4163/jnh.2015.48.4.310
|View full text |Cite
|
Sign up to set email alerts
|

Effects of natural eggshell membrane (NEM) on monosodium iodoacetate-induced arthritis in rats

Abstract: The aim of this study is to investigate anti-arthritis activity using natural eggshell membrane (NEM). Methods: NEM was administered at 52 mg/kg, 200 mg/kg, and 400 mg/kg to SD-Rat, where arthritis was induced by monosodium iodoacetate (MIA) at 3 mg. NO production in serum was measured using Griess reagent. Cytokines including IL-1β, and IL-6 were measured by Luminex and PGE 2, MMP-2, MMP-9, TIMP-1, LTB 4, and hs-CRP were measured by ELISA. The cartilage of patella volume was examined and 3-D high-resolution r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 25 publications
1
12
0
1
Order By: Relevance
“…Under the conditions of this study design, NEM was well tolerated with no obvious intervention-related adverse effects. These results obtained in a rat model of RA add to the growing body of evidence supporting the efficacy of NEM in arthritic rats and in humans with osteoarthritis [18,19,25,29].…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Under the conditions of this study design, NEM was well tolerated with no obvious intervention-related adverse effects. These results obtained in a rat model of RA add to the growing body of evidence supporting the efficacy of NEM in arthritic rats and in humans with osteoarthritis [18,19,25,29].…”
Section: Discussionsupporting
confidence: 66%
“…As reported by Sim et al, a higher dose of NEM was required (400 mg/kg/day) to reduce COMP in MIA arthritic rats than the dose administered in this study (52 mg/kg/day, representing the human equivalent dose of 500 mg per day). These findings suggest that either the MIA arthritic rat is a more severe model of arthritis, or that COMP is less sensitive to NEM, thereby exhibiting a dose response curve that is right-shifted [25].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“… 24 ESM is known to reduce the expression of various pro-inflammatory cytokines, including the key mediators of inflammation interleukin-1 beta (IL-1β) and tumor necrosis factor-alpha (TNF-α) both in vitro 25 and in vivo. 26 A proprietary form of ESM, commercially available as the branded product NEM ® (natural eggshell membrane); ESM Technologies, LLC, Carthage, MO, USA), has demonstrated safety and efficacy in multiple clinical trials in relieving joint pain and stiffness in humans with OA 27 29 and has been shown to reduce CTX-II levels in rat models of both OA 30 and RA 31 and in naturally occurring joint disease in dogs. 32 …”
Section: Introductionmentioning
confidence: 99%